2014
DOI: 10.4252/wjsc.v6.i4.467
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cells: A new source for brown and white adipocytes

Abstract: Mesenchymal stem cells (MSCs) derived from human induced pluripotent stem cells (hiPSCs) provide a novel source for generating adipocytes, thus opening new avenues for fundamental research and clinical medicine. We present the adipogenic potential of hiPSCs and the various methods to derive hiPSC-MSCs. We discuss the main characteristic of hiPSC-MSCs, which is their low adipogenic capacity as compared to adult-MSCs. Finally, we propose several hypotheses to explanation this feature, underlying a potential crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Interestingly, the low adipogenic differentiation potential is not restricted to hiPSC-derived cells as cells derived from human hESCs display the same feature, thus ruling out the possibility that the low hiPSC-adipogenic capacity could be due to incomplete reprogramming. The low adipogenic potential of adipose progenitors is also not dependent on the methods used to derive them from PSCs (31). Overall, these observations indicated that appropriate culture conditions had to be set up to unlock hPSC-BAP adipogenesis.…”
Section: Critical Role Of the Tgfβ Pathway In Hipsc-ba Progenitor Difmentioning
confidence: 90%
“…Interestingly, the low adipogenic differentiation potential is not restricted to hiPSC-derived cells as cells derived from human hESCs display the same feature, thus ruling out the possibility that the low hiPSC-adipogenic capacity could be due to incomplete reprogramming. The low adipogenic potential of adipose progenitors is also not dependent on the methods used to derive them from PSCs (31). Overall, these observations indicated that appropriate culture conditions had to be set up to unlock hPSC-BAP adipogenesis.…”
Section: Critical Role Of the Tgfβ Pathway In Hipsc-ba Progenitor Difmentioning
confidence: 90%
“…Most of the current protocols for in vitro adipocyte differentiation of hiPSCs are based on generation of embryoid bodies and/or derivation of mesenchymal stem cells prior to adipose differentiation [ 124 ]. A strategy involving overexpression of adipogenic transcription factors has also been proposed [ 125 ], but this results in a bypass of developmental pathways and therefore hampers pathophysiological studies.…”
Section: New Cellular Tools To Study Adipocyte Development mentioning
confidence: 99%
“…PSCs represent a promising new source for white and brown adipogenesis (Elefanty and Stanley, 2012; Hafner, 2014). Adipogenic differentiation of hiPSCs has been accomplished similarly to ESCs by firstly allowing cells to form EBs and then exposing them to RA.…”
Section: Brown Adipogenesis Of Stem Cellsmentioning
confidence: 99%